Vacancy Induced Energy Band Gap Changes of Semiconducting Zigzag Single Walled Carbon Nanotubes - Dereli, Gulay; Eyecioglu, Onder; Sungu Misirlioglu, Banu (UNIV SUCEAVA, FAC ELECTRICAL ENG, 2017)
In this work, we have examined how the multi-vacancy defects induced in the horizontal direction change the energetics and the electronic structure of semiconducting Single-Walled Carbon Nanotubes (SWCNTs). The electronic structure of SWCNTs is computed for each deformed configuration by means of real space, Order(N) Tight Binding Molecular Dynamic (O(N) TBMD) simulations. Energy band gap is obtained in real space through the behavior of electronic density of states (eDOS) near the Fermi level. Vacancies can effectively change the energetics and hence the electronic structure of SWCNTs. In this study, we choose three different kinds of semiconducting zigzag SWCNTs and determine the band gap modifications. We have selected (12,0), (13,0) and (14,0) zigzag SWCNTs according to n (mod 3) = 0, n (mod 3) = 1 and n (mod 3) = 2 classification. (12,0) SWCNT is metallic in its pristine state. The application of vacancies opens the electronic band gap and it goes up to 0.13 eV for a di-vacancy defected tube. On the other hand (13,0) and (14,0) SWCNTs are semiconductors with energy band gap values of 0.44 eV and 0.55 eV in their pristine state, respectively. Their energy band gap values decrease to 0.07 eV and 0.09 eV when mono-vacancy defects are induced in their horizontal directions. Then the di-vacancy defects open the band gap again. So in both cases, the semiconducting-metallic - semiconducting transitions occur. It is also shown that the band gap modification exhibits irreversible characteristics, which means that band gap values of the nanotubes do not reach their pristine values with increasing number of vacancies.
Keywords: single-walled carbon nanotubes; order N tight-binding molecular dynamics; vacancy; energy band gap; electronic properties; TIGHT-BINDING METHODS; MOLECULAR-DYNAMICS; ELECTRONIC-PROPERTIES; AB-INITIO; DEFECTS; SIMULATIONS; DIAMETER; DENSITY; Computer Science; Engineering